The effect of context on synonymous codon usage in genes with low codon usage bias. - Bulmer, M (1990)
The effect of neighbouring bases on the usage of synonymous codons in genes with low codon usage bias in yeast and E. coli is examined. The codon adaptation index is employed to identify a group of genes in each organism with low codon usage bias, which are likely to be weakly expressed. A similar pattern is found in complementary sequences with respect to synonymous usage of A vs G or of U vs C. It is suggested that this may reflect an effect of context on mutation rates in weakly expressed genes.